The Dialectics of Transformation in Africa - Bongmba, E. author. aut Link
X, 310 p.
Keywords: A discussion of political and religious crisis in Africa, this book covers such topics as democratic transition, good governance, civil society and the African renaissance. Elias K. Bongmba proposes humanistic interventions centred on the recovery of interpersonal relations and seeks to understand the ongoing struggles in Africa.